2022
DOI: 10.1002/app.52927
|View full text |Cite
|
Sign up to set email alerts
|

Upscale recycling of nonwoven polypropylene waste using a novel blending method

Abstract: Waste management of the nonwoven polypropylene (PP) fabric has become an emerging issue due to its increased usage. This study presents the upscale recycling of PP nonwoven fabric scrap generated during medical‐grade disposable gown manufacturing. To prepare PP and carbon black (CB) nanocomposite, a two‐step novel melt blending process is used. A maximum density of 937 kg/m3, shore D hardness of 74.45, and highest improvement in UV degradation resistance with a carbonyl index of 0.40 is recorded at 2 wt% of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…Rezekne, Latvia Proceedings of the 14 th International Scientific and Practical Conference. Volume 3,[214][215][216][217][218] The results, compared with other authors [20] - [22], are reliable and no deviations were observed in the regression analyses. They may be used and applied in engineering practice.…”
Section: • Hardnessmentioning
confidence: 53%
“…Rezekne, Latvia Proceedings of the 14 th International Scientific and Practical Conference. Volume 3,[214][215][216][217][218] The results, compared with other authors [20] - [22], are reliable and no deviations were observed in the regression analyses. They may be used and applied in engineering practice.…”
Section: • Hardnessmentioning
confidence: 53%
“…It is well known that iPP is a semicrystalline multiphase polymer and its microstructures such as the crystallinity, crystal size, and crystal form, directly affect the mechanical properties of products 53 . Considering that its injection molded products have a typical skin‐core structure 54 and RHCM has a positive effect on the surface as mentioned, hardness is one of the most important mechanical properties affecting the application of iPP products 55 . As shown in Figure 9, comparing the changes of shore hardness (D scale) of CIM, RHCM60, and RHCM90 during photodegradation, it is found that the hardness of iPP samples increases with increasing mold temperature.…”
Section: Resultsmentioning
confidence: 99%
“…53 Considering that its injection molded products have a typical skin-core structure 54 and RHCM has a positive effect on the surface as mentioned, hardness is one of the most important mechanical properties affecting the application of iPP products. 55 As shown in Figure 9, comparing the changes of shore hardness (D scale) of CIM, RHCM60, and RHCM90 during photodegradation, it is found that the hardness of iPP samples increases with increasing mold temperature. Because the crystalline state of outermost layer of products plays a decisive role in hardness, as mentioned, RHCM changes the crystalline state of iPP.…”
Section: Effect Of Rhcm On Photodegradationmentioning
confidence: 87%